Ben Jonson's Reception of Lucian. Issue 2 (November 2019) - Miola, Robert S.
Abstract : Throughout his career Ben Jonson drew variously upon Lucian, whom he encountered in the mythographies as well as in several Greek and Latin editions he owned. Jonson's receptions take the form of glancing reminiscence in the masques, as Lucian supplies mythological decoration and literary conceit. They appear as transformative allusion in Cynthia's Revels, which draws upon several satirical Dialogues of the Gods, and in The Staple of News, which re-appropriates a favorite satirical dialogue, Timon, the Misanthrope, to satirize the greed of the news industry. Jonson practices an extended and creative imitatio of Lucian's fantastic moon voyages ( A True Story and Icaromenippus ) in his much neglected News from the New World Discovered in the Moon . And, likewise, Jonson reworks Lucian extensively for the action of Poetaster : The Carousal supplies the lascivious banquet of 4.5, and Lexiphanes, the humiliating purge of Crispinus. Jonson's rich engagement with Lucian comes to a climax in Volpone, which borrows directly from The Dream, and several Dialogues of the Dead . Here whimsical ancient satire enables stern moral allegory. Responding to Poetaster in Satiro-mastix, Thomas Dekker has Captain Tucca rebuke Horace (i.e. Ben Jonson) by sarcastically calling him "Lucian." Jonson, no doubt, took the proffered insult as the highest compliment.